Simulations of the Impact of Co-injected Gases on CO2 Storage, the SIGARRR Project: Processes and Geochemical Approaches for Gas-water-Salt Interactions Modeling. (July 2017) - Corvisier, Jerome; Hajiw, Martha; Ahmar, Elise El; Coquelet, Christophe; Sterpenich, Jérôme; Privat, Romain; Jaubert, Jean-Noël; Ballerat-Busserolles, Karine; Coxam, Jean-Yves; Cézac, Pierre; Contamine, François; Serin, Jean-Paul; et al.
Abstract: The composition of the captured CO2 mixture may considerably vary both qualitatively and quantitatively depending on the sources, the selected technologies for purification... Many other compounds could be co-captured at various concentration levels and their potential co-storage along with CO2 could be considered. Since these compounds may change the behavior of the CO2 rich mixture, operators of the whole CCTS chain therefore wait for clear recommendations in terms of admissible concentration levels for the various co-injected impurities while regulators need tools allowing them to formulate these recommendations. The SIGARRR project aims at conducting precise geochemical simulations to model the long-term behavior of co-injected gases within CO2 storage sites based on a combination of experimental and numerical approaches, to ensure the reliability of numerical simulations. Within this context and the recent improvements in both processes and geochemical codes, this paper presents the water solubility precise calculations for CO2 and most of the potential impurities N2, O2, Ar, CO, H2 S, SO2, CH4, H2 and the brine solubility relatively accurate geochemical simulations for CO2, N2, O2 and CH4 as well.